The Prologue in Latin comedy: from Plautus to Romañá - Molina Sánchez , Manuel (Cuadernos de Filología Clásica. Estudios Latinos, 2024)
The following pages deal with the evolution of the Prologue in Latin comic works from Antiquity to the Renaissance. We examine the main features of the old palliata, the innovations introduced by Terence, its continued presence in Medieval comedy and the variety of Prologues to be found in the different varieties of Humanistic comedy. Despite the changes which it has undergone, we can claim that the Prologue has kept to a similar structure from its origin up to the Renaissance. It has continued to function unchanged as a preliminary paratext whose aim is to inform the receiver about the circumstances surrounding the work.